2018
DOI: 10.1186/s12906-018-2094-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective and restorative effects of the traditional Chinese medicine Jitai tablet against methamphetamine-induced dopaminergic neurotoxicity

Abstract: Our results indicated that JTT protects against METH-induced neurotoxicity and restores the dopaminergic function, and thus might be a potential treatment for the dopaminergic deficits associated with METH abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…As expected, GQD treatment can significantly attenuate anxiety level in Meth-withdrawn mice. Although a few reports were concerning the roles of TCM (mostly monomer) in antagonizing Meth associated neuro-damages [ 38 42 ], this study, to our knowledge, firstly reported that GQD mitigated the Meth withdrawal neurobehavioral abnormalities. Recently, by improving the compositions of gut microbial, GQD shows a desirable therapeutic effect on diseases like diabetes, cancers, ulcerative colitis, obesity and hypertension [ 18 22 ].…”
Section: Discussionmentioning
confidence: 62%
“…As expected, GQD treatment can significantly attenuate anxiety level in Meth-withdrawn mice. Although a few reports were concerning the roles of TCM (mostly monomer) in antagonizing Meth associated neuro-damages [ 38 42 ], this study, to our knowledge, firstly reported that GQD mitigated the Meth withdrawal neurobehavioral abnormalities. Recently, by improving the compositions of gut microbial, GQD shows a desirable therapeutic effect on diseases like diabetes, cancers, ulcerative colitis, obesity and hypertension [ 18 22 ].…”
Section: Discussionmentioning
confidence: 62%
“…Recently, a Chinese herbal prescription was reported to upregulates the striatal DAT and attenuates stereotyped behavior of Tourette syndrome in rats [50]. In addition, another traditional Chinese medicine was noticed to exert the protective and restorative effects against methamphetamine-induced dopaminergic neurotoxicity: it attenuates the stereotyped responses and restores DAT expression to the normal level [51]. Together, it is a reliable belief that DAT inhibition, as well as the resulting DA accumulation, is a key mechanism underlying TD development.…”
Section: Discussionmentioning
confidence: 99%
“…23 Jitai tablets were purchased as a positive control drug of Traditional Chinese Medicine from Wuhan Ezhong Pharmaceutical Co., Ltd. (Hubei, China). [24][25][26] OA, clonidine hydrochloride tablets, and Jitai tablets were all prepared as warm water suspensions. Morphine hydrochloride solution for injection was obtained from Shenyang No.1 Pharmaceutical Co., Ltd. of Northeast Pharmaceutical Group (Liaoning, China).…”
Section: Materials and Methods Chemicalsmentioning
confidence: 99%